Examining the Social Properties of Oklahoma Agricultural Facebook Pages: A Quantitative Content Analysis - Audrey E. H. King; Quisto Settle (Journal of Applied Communications, 2020)
Social media is used by millions of people in the United States, and producers are often encouraged to maintain a social media presence to promote their businesses and agriculture in general. Farmers have deeply entrenched identities. Social identity theory states people self-sort into certain groups. Social comparison and positive distinction are two principles of social identity theory. There is a need to research how agricultural operations are portraying those identities, including how they portray the identities of dissimilar agricultural operations online. This study compared Oklahoma mainstream and alternative producers in a quantitative content analysis of their Facebook pages. The following objectives guided this study: 1) Describe the agricultural operations in Oklahoma present on Facebook, 2. Describe the Facebook presence of agricultural operations in Oklahoma, 3) Describe operations’ expression of social-identity via Facebook, and 4) Compare the communication of alternative and mainstream agricultural operations in Oklahoma. Results of this study indicate that overall agricultural operations do not post frequently. While operations were likely to use positive distinctions to distinguish products from others, they were not likely to use social comparison. Moreover, there were not major differences between mainstream and alternative producers. Qualitative research exploring producers’ sense of identity would be valuable. Future studies should also explore the personal pages of agricultural producers, how producers use other social media outlets, and how the results of this study compare to other states’ producers.
Keywords: content analysis; social identity; social comparison; Facebook; social media